(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
The article is based on the scientific research of the essence and regulatory legal bases of investment activity, revealing the conditions and factors of increasing investment activity in small industrial zones, studying the foreign experiences of increasing investment activity in small industrial zones and considering the possibilities of use.